The Arctic - is the international bone of contention - Guben , M. G.; Губін, М. Г.; Губин, М. Г. (Одеса : Фенікс, 2012)
So, it is important to emphasize, that including the fact to the extent that the climate in the Arctic is getting warmer, the relations between the countries of the Arctic region become colder. And that is instead of to get together to fight with the negative effects of global warming. It is predicted, that after formation of the large ice floes in response to warming there would be destroyed the oil and gas platforms; and the construction of a new infrastructure would be absolutely complicated. It is also expected to strengthen the windshield for navigation and the possibility of individual sections of ice covering the Northern Sea Route; also it is unknown the role of dynamics of the ice sheets to the sea level rise and the fate of the carbon in the permafrost. And that’s not to mention the fact what a threat to native fauna would be, and what radical changes would occur in the life of the local indigenous peoples. I am fully confident, that these problems must be solved first of all by the whole world to save life on the planet Earth.
Guben M. G. The Arctic - is the international bone of contention / M. G. Guben // Міжнародні читання з міжнародного права пам’яті професора П.Є. Казанського : матер. третьої міжнар. наук. конф. (м. Одеса, 2–3 листопада 2012 р.) / відп. за випуск М. І. Пашковський ; НУ «ОЮА». – Одеса : Фенікс, 2012. – С. 522-524.
Keywords: Arctic; the Arctic - is the international bone of contention; Арктика как источник международного конфликта; Арктика; Арктика як джерело міжнародної напруженості